2021
DOI: 10.1111/echo.15013
|View full text |Cite
|
Sign up to set email alerts
|

Introducing echocardiography to medical students: A novel echocardiography E‐Learning experience

Abstract: Echocardiography is fundamental to the understanding and practice of cardiology. Traditionally, echocardiography is taught at the postgraduate level, mainly during cardiology fellowship. 1 The creation of hand-held ultrasound has made ultrasound learning more popular and expanded to residency and medical school levels. 2 Small studies suggested that learning cardiac ultrasound and/or point-of-care ultrasound during medical school was feasible [3][4][5][6] and can help improve understanding of cardiac physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
0
10
0
2
Order By: Relevance
“…The data obtained in the second test show a significant increase in technical knowledge in the course group in comparison with the control group, a finding that is also consistent with the results for subjective competence assessments in the course group. Earlier studies also demonstrated this, although in the present study the training time and training formats were very different [22][23][24][25][26][27]30]. A possible extension of the present training curriculum, which was adapted from the DGAI guidelines [37], might be to use standardized digital tests as well as practical examination formats [61].…”
Section: Minmentioning
confidence: 50%
See 3 more Smart Citations
“…The data obtained in the second test show a significant increase in technical knowledge in the course group in comparison with the control group, a finding that is also consistent with the results for subjective competence assessments in the course group. Earlier studies also demonstrated this, although in the present study the training time and training formats were very different [22][23][24][25][26][27]30]. A possible extension of the present training curriculum, which was adapted from the DGAI guidelines [37], might be to use standardized digital tests as well as practical examination formats [61].…”
Section: Minmentioning
confidence: 50%
“…In general, written tests [ 20 , 22 , 24 , 25 , 30 ], practical examination formats [ 20 , 61 ], and self-assessments using questionnaires [ 61 ] are used to test improvements in skills. The test section on “figural intelligence” was intended to investigate whether the groups were comparable in relation to spatial orientation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, providing future physicians with skills on how to acquire and interpret cardiac-echo data is becoming highly expected in medical curricula [4][5][6]. To meet these expectations the Board of the Faculty of Medicine of the Jagiellonian University Medical College (JUMC), supported by recent literature on online teaching [7][8][9] and by the experience of successful implementation of ECG e-learning [10,11], introduced in 2020/2021 academic year a subject entirely dedicated to this field. The subject has been included in the program of the 5 th year of the 6-year JUMC Faculty of Medicine curriculum.…”
Section: Introductionmentioning
confidence: 99%